Pengaruh Model Game Based Learning Berbantuan Media Paper Mode Wayground terhadap HOTS Siswa Kelas V SD - Fahrizal, Muhammad Iqbal (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine the effect of implementing the Game Based Learning model supported by an educational game medium, namely Paper Mode based on Wayground, on students’ Higher Order Thinking Skills (HOTS) in IPAS learning. The research employed a quantitative approach with a Pre-Experimental design, specifically the One Group Pretest”“Posttest Design. The sample consisted of 27 fifth-grade students at SD Negeri Karangroto 04. Data were collected through pretest and posttest instruments developed based on HOTS indicators within the cognitive domain, including C4 (analyzing), C5 (evaluating), and C6 (creating). The results revealed a significant improvement in students’ HOTS after the implementation of the learning model. The average pretest score was 41 with a learning mastery level of 3.7%, while the average posttest score increased to 76 with a mastery level of 70.37%. Furthermore, the Wilcoxon Signed Rank Test showed a significance value of 0.000, which is lower than 0.05, indicating a statistically significant difference between the pretest and posttest results. Therefore, it can be concluded that the Game Based Learning model assisted by Paper Mode based on Wayground is effective in enhancing students’ HOTS in IPAS learning.